Diabetes mellitus promoted lymph node metastasis in gastric cancer: a 15–year single-institution experience. Issue 8 (20th April 2022) - Chen, Xinhua; Chen, Yuehong; Li, Tao; Liang, Weiqi; Huang, Huilin; Su, Hongtao; Sui, Chuyang; Hu, Yanfeng; Chen, Hao; Lin, Tian; Chen, Tao; Zhao, Liying; et al.
Abstract: Background: Previous studies have revealed that diabetes mellitus (DM) promotes disease progress of gastric cancer (GC). This study aimed to further investigating whether DM advanced lymph nodes (LNs) metastasis in GC. Methods: The clinicopathologic data of GC patients with >15 examined LN (ELN) between October 2004 and December 2019 from a prospectively maintained database were included. The observational outcomes included the number (N3b status) and anatomical distribution (N3 stations) of metastatic LN (MLN). Results: A total of 2142 eligible patients were included in the study between October 2004 and December 2019. N3 stations metastasis (26.8% in DM vs. 19.3% in non-DM, P = 0.026) and N3b status (18.8% in DM vs. 12.8% in non-DM, P = 0.039) were more advanced in the DM group, and multivariate logistic regression analyses confirmed that DM was an independent factor of developing N3 stations metastasis (odds ratio [OR] = 1.771, P = 0.011) and N3b status (OR = 1.752, P = 0.028). Also, multivariate analyses determined DM was independently associated with more MLN (β = 1.424, P = 0.047). The preponderance of N3 stations metastasis (DM vs. non-DM, T1–2: 2.2% vs. 4.9%, T3: 29.0% vs. 20.3%, T4a: 38.9% vs. 25.8%, T4b: 50.0% vs. 36.6%; ELN16–29: 8.6% vs. 10.4%, ELN30–44: 27.9% vs. 20.5%, ELN ≥ 45: 37.7% vs. 25.3%), N3b status (DM vs. non-DM, T1–2: 0% vs. 1.7%, T3: 16.1% vs. 5.1%, T4a: 27.8% vs. 19.1%, T4b: 44.0% vs. 28.0%; ELN16–29: 8.6% vs. 7.9%, ELN30–44: 18.0% vs. 11.8%, ELN ≥ 45: 26.4% vs. 17.3%), and the number of MLN (DM vs. non-DM, T1–2: 0.4 vs. 1.1, T3: 8.6 vs. 5.2, T4a: 9.7 vs. 8.6, T4b: 17.0 vs. 12.8; ELN16–29: 3.6 vs. 4.6, ELN30–44: 5.8 vs. 5.5, ELN ≥ 45: 12.0 vs. 7.7) of DM group increased with the advancement of primary tumor depth stage and raising of ELN. Conclusions: DM was an independent risk factor for promoting LN metastasis. The preponderance of LN involvement in the DM group was aggravated with the advancement of tumor depth.